2019
DOI: 10.1038/s41598-019-43356-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of gut microbiota in shaping the relapse-remitting and chronic-progressive forms of multiple sclerosis in mouse models

Abstract: Using a mouse model of multiple sclerosis (MS), experimental autoimmune encephalitis (EAE), we evaluated the role of gut microbiota in modulating chronic-progressive (CP) versus relapse-remitting (RR) forms of the disease. We hypothesized that clinical courses of EAE may be shaped by differential gut microbiota. Metagenomic sequencing of prokaryotic 16S rRNA present in feces from naïve mice and those exhibiting CP-EAE or RR-EAE revealed significantly diverse microbial populations. Microbiota composition was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 48 publications
9
49
0
Order By: Relevance
“…The effects of probiotics on the host immune system could be also mediated by a modulation of the gut microbiota; indeed, several studies reported alterations in bacterial taxonomical composition in stools from patients and from animal models (54,55), suggesting an important role of microbiota in (auto)immune diseases. To our knowledge, this is the first study that characterize the intestinal microbiota composition in the Lewis rat EAMG model, considering also the effect of a probiotic therapeutic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of probiotics on the host immune system could be also mediated by a modulation of the gut microbiota; indeed, several studies reported alterations in bacterial taxonomical composition in stools from patients and from animal models (54,55), suggesting an important role of microbiota in (auto)immune diseases. To our knowledge, this is the first study that characterize the intestinal microbiota composition in the Lewis rat EAMG model, considering also the effect of a probiotic therapeutic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst others, the genus Parabacteroides was significantly more abundant in the gut microbiota of N+ responders compared to N+ non-responders . Notably, a recent study conducted in murine models of RMS and chronic-progressive MS identified Parabacteroides as more abundant in the gut microbiota of control mice [52]. Additionally, a previous study detected a significant reduction of Parabacteroides populations in the faecal microbiota of 71 MS patients not undergoing immunesuppressive treatment compared to that of 71 healthy control subjects [53].…”
Section: Gut Microbial Differences Between N+ Responders and N+ Non-rmentioning
confidence: 96%
“…. A potential pro-inflammatory role has been proposed for this genus [40] what could be related to a reduced incidence of enteric disorders when feed restriction is applied.…”
Section: Administration Of Antibiotics Impact On Some Taxa Relative Amentioning
confidence: 99%